At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
what do the instructions say to do?
solve the equation by completing the square
Solve the equation by completing the square. (1) x^2-4x+3=0 First, lets add -3 to both sides and we have: x^2-4x=-3 Now why did we do that? If you look at the left side of the equation only, you will see that its actually a quadratic equation that's missing the "C" term. We are going to choose a new "C" for the left side of the equation and add it to both sides thereby creating a new quadratic equation on the left side that's a perfect square. We'll take 1/2 of the "B" term(1/2)(4) or 2 and square it (2^2=4) and add this to both sides of the equation: x^2-4x+4=-3+4 or (x-2)^2=1 take sqrt of both sides x-2=+or-sqrt(1) or x-2=+or-1 now add 2 to both sidess x=2+or-1 x=2+1=3 and x=2-1=1 ck substitute in (1) 3^2-4(3)+3=0 9-12+3=0 -3+3=0 0=0 1^2-4(1)+3=0 1-4+3=0 -3+3=0 0=0 Hope this helps.
well, looks like your problem is solved ^_^'
or you could do this. 4x^2-x-3=0 4(x^2-x/4-3/4)=0 4(x^2-x/4+1/16-1/16-3/4)=0 4((x-1/8)^2-1/64-3/4)=0 4((x-1/8)^2-49/64)=0 4(x-1/8)^2-4(49/64)=0 4(x-1/8)^2-49/16=0 4(x-1/8)^2=49/16 (x-1/8)^2=49/64 x-1/8 = sqrt(49/64) or x-1/8=-sqrt(49/64) x-1/8 = 7/8 or x-1/8 = -7/8 x = 7/8+1/8 or x = -7/8+1/8 x = 8/8 or x = -6/8 x = 1 or x = -3/4 Answers are x=1 or x=−3 /4
Im starting to understand, but what would the answer be then?
Even though this is completing the square you could check your answers by factoring. x^2+4x+3 (x-3)(x-1) x=1, 3
i told you either x=1 or -3/4
*(x+1)(x+3) sorry about that
can we do another one?
yea sure :)
b=-10 a=1 c=-5